Numerical Study of Wave Reflection by The Curtain Wall-Pile Breakwater Using the SPH Model - Tahalele, Marcio; Satiti, Inggrit Tri Trida Wahyu; Khaldirian, Muhammad Farizqi (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
The Curtain Wall-Pile Breakwater (CPB) is comprised of a precast concrete wall structure that is upheld by pillars. The effectiveness of this breakwater has been extensively examined through experimental and numerical approaches in comparison to the conventional gravitational breakwater due to its reduced underwater footprint, which could be more environmentally sustainable. A Smoothed Particle Hydrodynamics (SPH) model using the open-source algorithm DualSPHysics is presented in this paper to simulate wave reflection on a CPB for multiple variables. This study focused on assessing the CPB’s performance in reflecting wave energy represented by the reflection coefficient (Cr), with a detailed investigation of two key parameters: relative depth, which is the ratio of wall depth to water depth (h/d) and wave steepness (Hi/L). The physical model was also tested in a laboratory flume to confirm the accuracy of the simulation results obtained through SPH. A fluid particle size of 0.5 cm was used, resulting in a simulation comprising approximately 9,320,717 particles. The results indicate that the Cr is directly proportional to the h/d and significantly influenced by Hi/L. Specifically, changes in h/d from 0.0 to 0.7 resulted in Cr increases from approximately 0.21 to 0.49 for lower wave steepness (Hi/L = 0.0097) and from approximately 0.36 to 0.60 for higher wave steepness (Hi/L = 0.0499). The quantitative analysis based on the quadratic regression equations shows that both the relative depth and wave steepness significantly influence the effectiveness of the CPB. The reflection coefficient increases with the relative depth, with a more significant effect observed for higher wave steepness. These findings underline the importance of considering both parameters in the design and optimization of breakwater structures to ensure robust and effective coastal protection.